(untitled) (Third Sector Social Economic Review, 2018)
The main purpose of this research is to analyze competitive power of Turkish production industry by comparative advantage method. In this research, 2001-2007 period is studied and HS2 classification is used. We used revealed comparative advantage, revealed symmetric comparative advantage and trade equilibrium index and create product map. As a result of our analyzes Turkey is net exporter in 34 chapters according to revealed comparative advantage, 31 chapters according to revealed symmetric comparative advantage and 19 chapters according to trade equilibrium index. According to chapter numbers the comparative advantage rate is % 46, the competitiveness ratio is % 42, net export power ratio is % 26 in Turkey’s industrial sector. In product map which is created by revealed symmetric comparative advantage and trade equilibrium index the number of A group chapter in which Turkey is net exporter is 19. In B group which Turkey is comparative but not in sufficient level there are 12 chapters. In D group which Turkey has not competitive advantage and net exporter there are 42 chapters. According to production industry map the share of Turkey in global foreign trade is not in expected level.